Penguatan Kemandirian Kesehatan melalui Edukasi Pemanfaatan Tanaman Obat Keluarga pada Masyarakat Terdampak Bencana Tanah Bergerak di Desa Mendala, Sirampog - Ikrima Khaerun Nisa; Nur Rahmah Hidayati; Isna Qutoruayun; Zulfa Nuristina; Dhea Muqadasah Ahmad; Jihan Puspita Sari; Nur Kholik Alipianto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Improving public health can be achieved by exploring the potential of local resources, including Family Medicinal Plants (TOGA) in the field or yard of the house. The importance of TOGA benefits is not commensurate with the community's knowledge of how to use them. This community service activity aims to increase public awareness of TOGA use and to improve the economic situation of Mendala Village residents after the disaster. The methods in this community service include administering a pretest, providing educational materials on TOGA use, conducting discussions and question-and-answer sessions, and concluding with a posttest. The target audience for this community service activity includes housewives with educational levels ranging from junior high school to a bachelor's degree, totaling 14 participants. The results of the Wilcoxon analysis showed a significant difference between pre- and post-education in TOGA use, with an average increase in knowledge from 75.00 to 92.86. The results of this community service indicate that education based on local potential can benefit the community by enabling the development of existing resources into economic value.